Maze learning and memory in a decapod crustacean. (23rd October 2019) - Davies, Ross; Gagen, Mary H.; Bull, James C.; Pope, Edward C.
Abstract : Spatial learning is an ecologically important trait well studied in vertebrates and a few invertebrates yet poorly understood in crustaceans. We investigated the ability of European shore crabs, Carcinus maenas, to learn a complex maze over four consecutive weeks using food as a motivator. Crabs showed steady improvement during this conditioning period in both the time taken to find the food and in the number of wrong turns taken. Crabs also clearly remembered the maze as when returned two weeks later but without any food, they all returned to the end of the maze in under 8 min. Crabs that had not been conditioned to the maze (naive animals) took far longer to reach the end, and many (42%) did not venture to the end of the maze at all during the 1 h study period. This study provides an initial description of spatial learning in a benthic decapod; a better appreciation of this adaptive trait in these animals will develop our understanding of resource exploitation by benthic crustaceans and their ecological roles.